Water problem in Central Asia: case study of Chu and Talas rivers (International relations and international law Journal, 2016)
After gaining independenceCentral Asian statesfaced the problem of joint use of water flows. Since then nation states became responsible for management on transboundary rivers. The water sharing regime and barter arrangements, which was working during the Soviet time, was interrupted. Authors consider the development of water relations among states of the region after the collapse of the USSR, notice critical moments, and also underline positive steps in water realtions between states. Authors emphasize their attention on the role of joint bodies and principles sharing the benefits and spendings in joint use of international water flows. The development of relations in Chu and Talas river basins between Kazakhstan and Kyrgyzstan, and joint commission on this rivers as well is taken as an example of successful joint water use.
Keywords: transboundary rivers; Central Asia; joint water use; water problem; Chu; Talas